Research integrity: Why is it so difficult to celebrate excellence instead of 'just stealing'. - Cronje, Franci (My University, 2014)
One of the most challenging issues for students to understand is that plagiarism should be avoided at all costs; furthermore, that the mere avoidance of plagiarising is not furthering the cause of academic enquiry. The quest needs to be to acquire the skill of referencing and synthesising arguments that would prove not only respect to the original creator of intellectual property, but also the ability to use a body of knowledge in order to create new insights. Therefore, adding any value to your argument not only means that one should not steal other people’s intellectual property, but that the academic argument relies on referring and building one’s own search on researching and strengthening a view with the solid foundation of expert opinion. Although the aspect of plagiarism in academic research seems to be the first, most prominent issue surfacing when the subject of research integrity is mentioned, it also seems to be the most pressing, basic hurdle with which the most undergraduate students battle. Why therefore, is plagiarism so prevalent? Might it be that we as current society produce an exponential amount of academic output? I suspect that the aforementioned is but one of the reasons we encounter the prominence of plagiarism not only in postgraduate work, but also in undergraduate production. The fact that digital searches makes it increasingly easier to detect the ‘borrowing of ideas’ and downright copying of text, sound and image, highlights the occurrence of the phenomenon. This paper will consider the basic ground rules of academic integrity with regards to intellectual property and why undergraduate students regularly fall prey to wrong practices. In light of this background, I would then propose a philosophical way forward: A mind shift as to the approach to celebration and acknowledging intellectual property.
Keywords: Plagiarism; Academic integrity; Academic success; Research; Plagiarism prevention; Intellectual property; Referencing